Álvaro Siza's First Encounter with Alvar Aalto - Ana Luísa de Sá (Joelho)
This paper delves into the use of references in architecture. By being particularly open about this often controversial subject,  lvaro Siza proposes fascinating and important materials for reflection. This paper parses two takes on his use of references as particularly posited by theorists William Curtis in 1994 and Peter Testa a decade before him. It expands on the seminal relevance of Siza’s first encounter with Alvar Aalto. It argues the implications of the event, both immediate and yonder, highlighting, through Siza’s own words, clues to underlying processes in his (re)collection of references as an instrument of work. It readdresses Siza’s use of references in light of the complexities of the phenomena at play. This paper portrays a fragment of an ongoing research into Álvaro Siza’s modus pensandi and modus faciendi.